The Role of Job Resources in Enhancing Work Engagement: The Mediating Effect of Job Satisfaction - Amanda, Velia; Zamralita, Zamralita; Fahlevi, Reza (International Journal of Multidisciplinary Research of Higher Education, 2026)
Human resources are a strategic asset that must be managed effectively to sustain organizational performance. Strengthening employee engagement requires not only productivity and motivation but also the provision of adequate job resources. Yet, global evidence shows persistent challenges, with engagement levels remaining low and employees reporting limited vigor, dedication, and absorption. This study investigates the influence of job resources on work engagement, with job satisfaction as a mediating factor. A quantitative approach was employed using convenience sampling, involving 350 employees in Indonesia. Data were collected through an online survey using validated instruments for measuring work engagement, job resources, and job satisfaction. The findings reveal that job resources significantly and positively affect work engagement, and job satisfaction partially mediates this relationship. These results highlight the importance of organizational strategies that prioritize job satisfaction as a pathway to strengthening employee engagement and sustaining long-term performance.